PENETAPAN KAWASAN TEMPAT SUCI DAN KAWASAN PARIWISATA DALAM PENATAAN RUANG DI BALI - I Ketut Sudiarta (Faculty of Law, Universitas Diponegoro, 2011)
There are three major components within the space management that is reciprocally-related, they are: planning, utilizing, and space-controlling. Within the space management that takes place in the local sector, the aspect of planning belongs to the authority of the provincial government to uphold, meanwhile, the aspect of utilizing and space controlling are to be endorsed by the city or regency governing and administration. In the Province of Bali, the planning of space management has been arranged based upon the Local Regulation of Bali Province No 16 Year 2009. Within this regulation, there has been an overlapping conception regarding the enactment of the region of the holy places with the region of tourism. Among ten (1O) regions of holy places that have been stated by this regulation, there has been only one region of holy place that suits and consistent based upon its utility, which is being utilized as the region of holy place. On the other hand, the other nine (9) remaining region of holy places status have a/so been enacted as the region of tourism.